Information and Communication Technology (Ict) As a Necessity for Libraries and Librarians of Nigerian Universities in the 21st Century - Okon, Michael E; Ogbodo, Catherine I (Review of Information Engineering and Applications, 2014)
ICTS have transformed all services in all sectors of the global economy. Library services have not been exception. In deed ICTS have revolutionized the manner information is processed, stored, retrieved and transferred to the would be users. This paper examines ICT as a necessity for libraries and Librarians in Nigerian Universities in the 21st century. Information and Communication Technology may be seen as the hardware and software that enables the society to create, collect, consolidate and communicate information in multi-media formats for variety of purpose. The paper examines the impact of ICT in libraries to include creation of On-line Public Access Catalogue (OPAC), creation of virtual libraries and Institutional Repository, resource sharing, networking and for electronic theft detector system. The efforts of government at developing ICT infrastructure through the National Virtual (Digital) library project and the Nigerian Research Education Network(Ngren) which resulted in promoting the low ICT skills of Nigerian librarians is commendable. The paper suggested an intensive in- house training by individual university library management for librarians as a means of increasing their ICT skills.